CHARACTERISTICS AND EFFECTIVENESS OF CHITOSAN ORININATED FROM THE CARAPACE OF T. ANOMALA SHRIMP AS AN ANTIBACTERIAL COMPOUND - Tengku Muhammad Ghazali; Rahman Karnila; Dewita Dewita (Fakultas Perikanan dan Kelautan, Universitas Riau, 2019)
This study aims to investigate the inhibition zones of the chitosan against Pseudomonas aeruginosa. Carapace from T. anomala is used as raw material of chitosan. There were 5 treatments used, namely positive control (K0+), negative control (K0-), 5% chitosan (K1), 7% chitosan (K2) and 9% (K3) chitosan. The carapace was taken and then washed, dried, refined, demineralization, de-preoteinated, deasitelation and was tested using double layer method, discs and well diffusion. The proximate carapace test results were as follows, water content was 68.18 % gross wight (gw), moisture content 11.77 % dry wight (dw) protein content, 2.35 %dw fat content, 84.43 %dw ash content and carbohydrate content was 1.45 %dw. The chitosan of T. anomala characteristics were yellowish white flakes, odorless and tasteless with yield value, moisture content, ash content, mineral content (Ca, Fe, K, Na, P) and the degree of deacetylation 27.51 %; 7.31 %gw; 3.40 %dw; 12.17 mg/L; 4.90 mg/L; 3.40 mg/L; 5.49 mg/L; 0.27 mg/L; and 73.43 % respectively , Results on antimicrobial sensivity tests using double layer, disk blank and well diffusion. Shown clear zone, 13.87 mm, 11.34 mm and 14.62 mm. these values indicate that the antimicrobial effect of the chitosan is strong.